IMPACT OF MONETARY STIMULUS PACKAGE TO COUNTER ECONOMIC CRISIS – COVID 19 (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2022)
The Covid-19 outburst both supply and demand  shocks. Aggressive monetary stimulus that inject  liquidity and support investment can offset  the effect of demand and supply shock. Policy  makers in the developing economies must access  the efficiency and socioeconomic consequences  of the moderation policies. In the short run the  economic policy of the developing economy was  dedicated on providing crisis relief to vulnerable  population as in the short run it is not possible  to stimulate the system. The study’s goal is  to examine the impact of monetary stimulus  package for the Indian economy to kick-start  the economy out of the stagnation trap. This  paper is an exploratory research. The data used  in this paper is from the reports made by an  international and national organisation like  WHO, IMF, Report by Reserve bank of India,  articles from newspapers, interviews by the  experts in the field.
Keywords: liquidity; providing; anticipated